On the role of retrosplenial cortex in long-lasting memory storage - Katche, Cynthia Lorena (2013)
The retrosplenial cortex (RSC) is involved in a range of cognitive functions. However, its precise involvement in memory processing is unknown. Pharmacological and behavioral experiments demonstrate that protein synthesis and c-Fos expression in the anterior part of RSC (aRSC) are necessary late after training to maintain for many days a fear-motivated memory. Long-lasting memory storage is regulated by D1/D5 dopamine receptors in aRSC and depends on the functional interplay between dorsal hippocampus and aRSC. These results suggest that the RSC recapitulates some of the molecular events that occur in the hippocampus to maintain memory trace over time.